VIRAL INFECTIONS POSING SIGNIFICANT THREATS TO SWINE POPULATIONS IN INDONESIA AND GLOBALLY: A REVIEW - Fedri Rell; Andi Magfira Satya Apada; Baso Yusuf; Rian Hari Suharto; Abdul Wahid Jamaluddin (Buletin Veteriner Udayana, 2025)
Several viruses often infect pigs which can cause major losses for farmers. Viral infections in pigs can be subclinical, chronic and acute. Viral diseases in pigs often result in mass deaths on pig farms, causing economic losses and not only that, they can also threaten human lives depending on the virus variant that causes them. Various symptoms such as flu, fever, lack of appetite, paralysis, bleeding in various organs will be found according to the degree of severity. The purpose of this article is to describe several viral infections in pigs that are very threatening and have been reported to cause major losses for farmers, namely: African swine fever (ASF), hog cholera (HC), & Swine influenza (SI). African swine fever is a very contagious disease that arises due to infection with the genus Asfivirus virus of the Asfarviridae family which is encoded by double-stranded DNA genetic material. ASF disease is reported to have caused mortality in pig farms reaching 100%. Likewise, HC disease, also known as cholera disease in pigs, can be fatal in pigs with a mortality rate of up to 100%. In contrast to swine influenza, also known as swine flu, it is a viral disease that is chronic and zoonotic. It is reported that swine flu has triggered flu outbreaks in humans since 1918 until now. Various factors influence the level of disease spread, namely monitoring livestock traffic, biosecurity of cages, the presence of vaccinations and the presence or absence of vectors as well as the use of swill feed as animal feed. So knowledge is needed about the diseases that really threaten pigs which will have an impact on farmers' finances. The results of this literature review add to scientific references related to viral diseases in pig farming. In this way, it will increase knowledge for readers, breeders and academics so that they can provide prevention and control of viral diseases in pig farms. And also, it is expected that there is counseling from related instances about livestock health management in the prevention and control of diseases in pigs.